Entrepreneurship and Marketing Communication Mentoring for Post-Migrant Families in Resapombo Village, Blitar, East Java - Brahma Putra Pratama; Sherly Hindra Negoro; Nobertus Ribut Santoso; RA Vita Noor Prima Astuti; Sekhar Candra Pawana; Felix Bimo Aryoputro (Jurnal Atma Inovasia, 2026)
This mentoring program is addressed to former migrant families in Resapombo Village, Blitar, East Java, in response to the economic issue. The entrepreneurship and marketing communication program aims to create a resilient economy in remote areas. The methods used in this mentoring are socialization, workshops/training, cadre recruitment, and entrepreneurial practice. The primary materials presented in this mentoring program include building entrepreneurial thinking and spirit, canvas business models, creating brands and marketing communication planning, saving culture, and family financial management. The recruitment of cadres is essential in this activity to maintain the program's sustainability. Participants were asked to put their business ideas into practice, and then they were given insights into obtaining business capital for the last topic. It is designed to ensure that ideas can be realized and that economically resilient families can be realized.